2016
DOI: 10.3390/su8010043
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Business Models for Circular Economy—Towards the Conceptual Framework

Abstract: Switching from the current linear model of economy to a circular one has recently attracted increased attention from major global companies e.g., Google, Unilever, Renault, and policymakers attending the World Economic Forum. The reasons for this are the huge financial, social and environmental benefits. However, the global shift from one model of economy to another also concerns smaller companies on a micro-level. Thus, comprehensive knowledge on designing circular business models is needed to stimulate and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
941
0
80

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,120 publications
(1,030 citation statements)
references
References 46 publications
9
941
0
80
Order By: Relevance
“…Several existing conceptual frameworks explain why CE is the most effective way to go about material use (Murray et al, 2015;Lewandowski, 2016). However, there is no existing unified theory or conceptual approach on how CE can be implemented (Murray et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Several existing conceptual frameworks explain why CE is the most effective way to go about material use (Murray et al, 2015;Lewandowski, 2016). However, there is no existing unified theory or conceptual approach on how CE can be implemented (Murray et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Lewandowski (2016), claim that circular business models are widely seen at the core of CE. They are "the driving force in the shift towards [CE]" (EUKN, 2015).…”
Section: Enabler Of the Circular Economymentioning
confidence: 99%
“…These can blur the concept since they frequently operate in significantly different worlds of thought (Gladek, 2017;de Vries and Petersen, 2009). Blurriness has been raised as a criticism against concepts such as the green economy one (Loiseau et al, 2016) and it has also been raised against CE in various CE review articles we identified (Ghisellini et al, 2016;Lieder and Rashid 2016;Blomsma and Brennan, 2017;Sauvé et al, 2016;Murray et al, 2017;Geissdoerfer et al, 2017;Lewandowski, 2016; further details in Table 1) and beyond. For instance, Lieder and Rashid (2016, p.37) point out that "there are various possibilities for defining [CE]", while Yuan et al (2008, p.5) write that "there is no commonly accepted definition of [CE]".…”
Section: Introductionmentioning
confidence: 99%
“…Also, the embodied carbon emissions of the materials used to construct the building are not being optimised if a large portion of the building is consistently unused. As a consequence, desk-sharing has even been cited as a good example of the circular economy in the built environment [29]. Underutilised buildings can even contribute to urban sprawl and an example of this is the construction of new buildings on the edge of cities while many spaces that are already constructed remain unused.…”
Section: Corporate Real Estatementioning
confidence: 99%